english DETERMINANTS OF ADHERENCE TO ANTI-TUBERCULOSIS DRUGS (ATD) AT BALOI PERMAI PRIMARY HEALTH CENTER, BATAM - ELZUSANDRY FITHRI; Herdianti; Sabri; Hendri Herman (Journal of Hospital Administration and Management (JHAM), 2026)
Adherence to anti-tuberculosis drugs (ATD) therapy is a critical determinant of successful tuberculosis treatment and the prevention of drug resistance. Non-adherence may lead to treatment failure, disease recurrence, and continued transmission within the community. Therefore, identifying factors that influence patient adherence is essential for strengthening tuberculosis control programs. This study aimed to examine factors associated with adherence to anti-tuberculosis medication among pulmonary tuberculosis patients at Baloi Permai Primary Health Center, Batam City. A quantitative cross-sectional study was conducted involving 39 patients undergoing anti-tuberculosis treatment. Data were collected using structured questionnaires assessing knowledge, attitudes, practices, family support, and the role of health workers. Statistical analysis was performed using Chi-square tests and logistic regression. The bivariate analysis revealed that patient attitude (p = 0.050) and family support (p = 0.006) were significantly associated with treatment adherence. Meanwhile, knowledge, practices, and the role of health workers were not significantly related to adherence (p > 0.05). Multivariate analysis identified family support as the most influential factor affecting adherence to anti-tuberculosis therapy (OR = 6.03; p = 0.010). In conclusion, family support is the strongest determinant of ATD adherence. Strengthening family-based approaches should be integrated into TB management programs at primary healthcare facilities.